2006
DOI: 10.1515/bc.2006.075
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localisation of human inositol 1,4,5-trisphosphate 3-kinase C: species-specific use of alternative export sites for nucleo-cytoplasmic shuttling indicates divergent roles of the catalytic and N-terminal domains

Abstract: The three isoforms of human Ins(1,4,5)P3 3-kinase (IP3K) show remarkable differences in their intracellular targeting. Whereas predominant targeting to the cytoskeleton and endoplasmic reticulum has been shown for IP3K-A and IP3K-B, rat IP3K-C shuttles actively between the nucleus and cytoplasm. In the present study we examined the expression and intracellular localisation of endogenous IP3K-C in different mammalian cell lines using an isoform-specific antibody. In addition, human IP3K-C, showing remarkable di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This isoform is the least regulated by feedback from Ca 2ϩ /CaM and lacks a consensus phosphorylation site for CaM kinase. Thus, it has been suggested that IP 3 KC is adapted for regulating the resting Ins(1,4,5)P 3 levels in cells (42,43). The reported K m values for mammalian IP 3 Ks range from about 0.2 to 10 M (28, 38), whereas the K m reported for dmIP 3 K␤ is 25 nM (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This isoform is the least regulated by feedback from Ca 2ϩ /CaM and lacks a consensus phosphorylation site for CaM kinase. Thus, it has been suggested that IP 3 KC is adapted for regulating the resting Ins(1,4,5)P 3 levels in cells (42,43). The reported K m values for mammalian IP 3 Ks range from about 0.2 to 10 M (28, 38), whereas the K m reported for dmIP 3 K␤ is 25 nM (11).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IP 3 KB can associate with F-actin (41), but it can also be targeted to the endoplasmic reticulum (24), a targeting that may be dynamically regulated by proteases (25). IP 3 KC has been reported to be cytosolic in humans (24), yet it is also reported to actively shuttle between the cytoplasm and the nucleus in the rat (42,43).…”
mentioning
confidence: 99%
“…The secondary ␣-rabbit antibody was labeled with Alexa Fluor 488. DAPI staining and examination of the intracellular localization by epifluorescence microscopy were previously described by Nalaskowski et al (29). Transient transfection of eukaryotic cells was performed using the Metafectene reagent according to the manufacturer's instructions (Biontex Laboratories, Munich, Germany).…”
Section: Cloning and Mutagenesis Of Egfp Fusion Gene Expressionmentioning
confidence: 99%
“…Signal-The C isoform of human and rat IP3K is actively imported into and actively exported out of the nucleus of mammalian cells (29,30). Its nuclear export is mediated by leucine-rich nuclear export signals (NES).…”
Section: Active Nuclear Export Of Ip3kb Is Mediated By a Leucinerich mentioning
confidence: 99%
“…This is specific for ITPKC and was not observed with ITPKA and ITPKB. The mouse endogenous ITPKC protein was never detected in the nucleus, in contrast to previously reported data of transfected rat and human ITPKC in NRK 52E renal cells (Nalaskowski et al, 2003(Nalaskowski et al, , 2006. We also analyzed multiciliated tracheal epithelial cells and spermatozoa for ITPKC protein function in our Itpkc þ/þ and Itpkc À/-mice.…”
Section: Discussionmentioning
confidence: 73%